Describing financial toxicity among cancer patients in different income countries: a systematic review and meta-analysis - Azzani, Meram; Atroosh, Wahib Mohammed; Anbazhagan, Deepa; Kumarasamy, Vinoth; Abdalla, Mona Mohamed Ibrahim (Frontiers in Public Health, 2024)
Background: There is limited evidence of financial toxicity (FT) among cancer patients from countries of various income levels. Hence, this study aims to determine the prevalence of objective and subjective FT and their measurements in relation to cancer treatment. Methods: PubMed, Science Direct, Scopus, and CINAHL databases were searched to find studies that examined FT. There was no limit on the design or setting of the study. Random-effects meta-analysis was utilized to obtain the pooled prevalence of objective FT. Results: Out of 244 identified studies during the initial screening, only 64 papers were included in this review. The approach frequently employed to calculate the objective FT in the included research was catastrophic health expenditure (CHE). The method often used in the included studies to determine the objective FT was catastrophic health expenditure (CHE). The pooled prevalence of CHE was 47% (95% CI: 24.0-70.0) in middle-and high-income countries and the highest percentage was seen in low-income countries (74.4%). A total of 30 studies focused on subjective FT, in which nine of them used the COST tool (COmprehensive Score for FT) and reported median scores ranging between 17.0 and 31.9. Conclusions: This study shows that cancer patients from various income-group countries experienced a significant financial burden during their treatment. It is imperative to conduct further studies on interventions and policies that can lower FT caused by cancer treatment.